Occupational Safety and Health: A Systematic Literature Review (SLR) - Saqif Haidarravy; Annisa Aulia Apni; Helmi Buyung Aulia Safrizal (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this literature review is to find and examine various definitions of conflict management based on the broad context of previous research. This research was conducted qualitatively using the literature study method with the help of the Google Scholar and Mendeley databases. The type of data used in this literature review is a type of secondary data in the form of articles and research journals totaling 36 articles and international research journals with a publication range of 2015-2022. The results of this literature review are based on the results of bibliometric data analysis through the context of previous research which shows that there are 6 definitions of occupational safety and health (OSH), 3 antecedents of occupational safety and health (OSH), 6 consequences of occupational safety and health (OSH) and 12 sectors. occupational safety and health (OSH)